2020
DOI: 10.3390/ijms21114042
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Complexes as Contrast Agent for Cellular NMR Spectroscopy

Abstract: Aqua Gd3+ and Gd-DOTA (gadolinium-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacete) complexes were studied as a contrast agent in cellular NMR (nuclear magnetic resonance) spectroscopy for distinguishing between intracellular and extracellular spaces. The contrast agents for this purpose should provide strong paramagnetic relaxation enhancement and localize in the extracellular space without disturbing biological functions. Cell membrane permeability to Gd complexes was evaluated from the concentrations of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Gadolinium-based contrast agents have been widely used in MRI diagnostic imaging, for studying soluble proteins, for characterizing protein-protein, protein-oligosaccharides, and protein-nucleic acid complexes, and for investigating membrane proteins using NMR spectroscopy [ 26 , 27 ]. Sakol et al have also shown the utility of the Gd-based contrast agent, Gd-DOTA, for cellular localization studies using NMR spectroscopy [ 28 ]. Similarly, Mulder and colleagues utilized gadolinium-based PRE agents and achieved a 3- to 4-fold improvement in acquisition time for quantifying several plasma metabolites [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadolinium-based contrast agents have been widely used in MRI diagnostic imaging, for studying soluble proteins, for characterizing protein-protein, protein-oligosaccharides, and protein-nucleic acid complexes, and for investigating membrane proteins using NMR spectroscopy [ 26 , 27 ]. Sakol et al have also shown the utility of the Gd-based contrast agent, Gd-DOTA, for cellular localization studies using NMR spectroscopy [ 28 ]. Similarly, Mulder and colleagues utilized gadolinium-based PRE agents and achieved a 3- to 4-fold improvement in acquisition time for quantifying several plasma metabolites [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in T 1 and T 2 rates depends on the contrast agent used and its concentration, the charge state of the compound, the viscosity of the solution, and the protein affinity of either the compound or contrast agent, among other issues. The typical range of T 1 values for nuclei of common metabolites such as glucose, lactate, citrate, acetate, glutamine, and alanine are between 0.9 and 4 s. Similarly, T 2 values range from 100 to 600 ms [ 17 , 28 , 29 ]. In the presence of Gd, T 1 values can decrease from 2- to 10-fold depending on the concentration of Gd.…”
Section: Resultsmentioning
confidence: 99%
“…The macrocycle DOTA is considered one of the gold standards in nuclear medicine and in the last 25 years, DOTAbased chelators had a tremendous impact in various medical imaging modalities such as PET, SPECT, MRI and fluorescence imaging (6). Its widespread use is mainly due to its versatility that allows the complexation of different metal ions, but also to its easy functionalization, allowing the most diversified pre-clinical and clinical applications (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…These articles showcase recent advancements in the broader field of NMR. Fujiwara and coworkers work on emerging cellular NMR spectroscopy that has implications in elucidating structures and dynamics in native cellular environments [ 1 ]. These authors investigate contrast agents Gd 3+ and Gd-DOTA (gadolinium-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacete) probing molecules in E. coli cells in situ [ 1 ].…”
mentioning
confidence: 99%
“…Fujiwara and coworkers work on emerging cellular NMR spectroscopy that has implications in elucidating structures and dynamics in native cellular environments [ 1 ]. These authors investigate contrast agents Gd 3+ and Gd-DOTA (gadolinium-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacete) probing molecules in E. coli cells in situ [ 1 ]. Broker, Tompa, and coworkers construct melting diagrams, using a wide line NMR method, of intrinsically disordered pathogenic protein alpha-synuclein [ 2 ].…”
mentioning
confidence: 99%